Senators-Elect Urges Expulsion of Hungarian Delegates - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Emergency Committee for UN Action on Hungary Seven newly elected members of the US Senate have joined other members of Congress in endorsing the growing campaign to expel the Hungarian delegates from UN.